O new physics, where art thou?: A global search in the top sector - Brivio, Ilaria; Bruggisser, Sebastian; Plehn, Tilman; Westhoff, Susanne (Arxiv, 2019)
We provide a comprehensive global analysis of Run II top measurements at the LHC in terms of dimension-6 operators. A distinctive feature of the top sector as compared to the Higgs-electroweak sector is the large number of four-quark operators. We discuss in detail how they can be tested and how quadratic terms lead to a stable limit on each individual Wilson coefficient. Predictions for all observables are computed at NLO in QCD. Our SFitter analysis framework features a detailed error treatment and shows that theoretical uncertainties are a limiting factor.